A reverse logistics chain mathematical model for a sustainable production system of perishable goods based on demand optimization - Saeed Tavakkoli Moghaddam; Mehrdad Javadi; Mohammad Molana (Journal of Industrial Engineering International, 2019)
Sustainability in the supply chain means pushing the supply chain to focus on social, economic and environmental aspects, and addressing the existing problems in the traditional supply chain. Considering the importance of evaluating supply chain networks, especially in the field of perishable commodities, this paper aimed to design a mathematical model for the reverse supply chain of perishable goods, taking into account the sustainable production system. In this research, four objective functions were considered to maximize profitability and the level of satisfaction with the use of technology, minimize costs and measure environmental impacts. The results of the implementation of the proposed model for a manufacturing company show that objective functions are sensitive to demand, so the change in demand changes the objective functions, in particular the profitability function.
Keywords: 650; Reverse logistics chain network; Sustainable production system; Perishable products; Mathematical modeling